Factors Associated With Health-Related Quality of Life Among Cancer Survivors in the United States. Issue 1 (23rd January 2021) - Han, Xuesong; Robinson, L Ashley; Jensen, Roxanne E; Smith, Tenbroeck G; Yabroff, K Robin
Abstract: Background: With increasing prevalence of cancer survivors in the United States, health-related quality of life (HRQOL) has become a major priority. We describe HRQOL in a nationally representative sample of cancer survivors and examine associations with key sociodemographic, clinical, and lifestyle characteristics. Methods: Cancer survivors, defined as individuals ever diagnosed with cancer (N = 877), were identified from the 2016 Medical Expenditure Panel Survey-Experiences with Cancer Survivorship Supplement, a nationally representative survey. Physical and mental health domains of HRQOL were measured by the Global Physical Health (GPH) and Global Mental Health (GMH) subscales of the Patient-Reported Outcomes Measurement Information System Global-10. Multivariable linear regression was used to examine associations of sociodemographic, clinical, and lifestyle factors with GPH and GMH scores. All statistical tests were 2-sided. Results: Cancer survivors' mean GPH (49.28, SD = 8.79) and mean GMH (51.67, SD = 8.38) were similar to general population means (50, SD = 10). Higher family income was associated with better GPH and GMH scores, whereas a greater number of comorbidities and lower physical activity were statistically significantly associated with worse GPH and GMH. Survivors last treated 5 years ago and longer had better GPH than those treated during the past year, and current smokers had worse GMH than nonsmokers (all β > 3 and all P  <   .001). Conclusions: Cancer survivors in the United States have generally good HRQOL, with similar physical and mental health scores to the general US population. However, comorbidities, poor health behaviors, and recent treatment may be risk factors for worse HRQOL. Multimorbidity management and healthy behavior promotion may play a key role in maximizing HRQOL for cancer survivors.